Memorex in the Neonatal Resuscitation Program (NRP). hottest recommendations from NRP 8th edition 2021 - Mohamed, Mossad Abdelhak Shaban; Rosternburghe, Hans; Ramli, Noraida; Ibrahim, Roshidah; Abdelhalim, Abdelbaset Taher (2021)
Background: Optimal neonatal resuscitation in the first few minutes of life (the Golden minutes) can save critically ill neonates. Presentation: additional new steps include the Resuscitation Quality Improvement Program (RQI) focusing on the skill of positive pressure ventilation. The four pre-birth questions are Gestational age, clear Amniotic fluid, Additional risk factors, and Umbilical cord management plan. Initial steps fulfil Warm, dry, stimulate, position airway and, suction if needed. When an alternative airway becomes necessary, a cardiac monitor is essential. The initial IV or IO dose of epinephrine is 0.02 mg/kg (equal to 0.2 mL/kg). The endotracheal epinephrine dose equal to 0.1 mg/kg (1 mL/kg). Flush IV/IO epinephrine with 3 mL normal saline for all babies. Support skin-to-skin care for bonding, breastfeeding and normothermia. If the confirmed absence of HR after all appropriate steps are performed, consider cessation of resuscitation efforts around 20 minutes after birth (Initiate discussion with the family). Unchanging steps, a qualified person or resuscitation team should attend every delivery. Establish briefing, delegate workload, and check equipment. Key behavioural skills, including the call for help. Upon delivery, a rapid assessment is the baby term, muscle tone and breathing or crying, then commencing the initial steps. Use plastic wrap for less than 32 weeks. Lung Ventilation and Ventilation Corrective Steps (MRSOPA) is the critical steps. Adjust suction pressure from 60-100 and the flowmeter to 10 L/min, oxygen with 21%, increased judiciously guided by preductal saturation. If the heart rate is less than 60 despite adequate 30-second ventilation intubate, start chest compression for 60 seconds by two thumbs technique. If still bradycardic, give the medications. Delayed cord clamping of stable babies and avoid cord milking in preterm. Conclusion: NRP regulations changed according to evidence-based medicine. The latest NRP edition will help all institutions